Economic revival in North and East Sri Lanka: what are the impediments? - Sarvanathan, Muttukrishna (2003)
The government of Sri Lanka imposed an economic embargo on the N and E province in 1999 covering a range of consumer goods including fuel, food and medicine. The embargo created an informal market for these goods. More importantly it allowed the Liberation Tigers of Tamil Eelam to play a dominant role in the management of the economy in the territory, leading to a dual economic system, a command economy in the north and east and a private sector-led liberal market economic model in the rest of the country. It is now a year since the economic embargo has been lifted. How has it affected the economy of N and E province? What are the factors inhibiting economic revival in this region? - Reproduced.
Keywords: Economic reform - Sri Lanka; Economic reform